A (re)significação do agir do estagiário de Língua Portuguesa - Monte Filha, Maria Vieira (2019)
This research analyzes how the intern re-signifies his acting during the Teaching Internship in Portuguese Language. In order to reach this goal, we have four guiding questions: What are the constitutive elements of the intern acting? Which expertises are mobilized by the intern as he reflects on his acting and describes it? How the intern reveals the representations about acting and teaching? And how the intern positions himself as long as he reflects on his acting in the classroom? For each question, we set a specific goal and elect analytical categories which allow us to reach it. Our theoretical-methodological reference is the Socio-Discursive Interactionism, focusing on the studies of Bronckart (1999, 2006, 2009) and Buela (2007, 2010, 2016), and we also made use of the concepts of the acting of teaching, didactic repertoire (CICUREL, 2011) and the expertises (SCHNEUWLY; HOFSTETTER, 2009; VANHULLE, 2009; 2009a). The elect analytical categories are: thematic content, expertises, voices and agentivity marks, modalizations. For our data generation, we counted on the participation of four students of the Portuguese Language Graduation course of the Universidade Federal do Ceará (UFC), who were attending internship classes. The methodology used is in descending direction, which means, it goes from global to local, from bigger unity to inferior level unities. Assuming that it is possible for the intern to develop a particular acting during the conducting classes, which turns out to be different from the acting of teaching, the results point out to the existence of particular elements of the acting of the intern and he reveals them when reflecting on his practical classes, there is increasing concern regarding the expertise to teach in relation to institucional expertise and teaching expertise. As regards the enunciative mechanisms, the interns reveal a measure of enunciative responsibility following a scale of implication and protagonism and present in their representations about the acting the four types of modalizations, getting relative emphasis to appreatitives, deontics and pragmatics in this order.